Property Values and the Likelihood of Self-Employment - Åsa Hansson; Fredrik Kopsch (Research Institute of Industrial Economics (IFN), 2020)
It is well known that capital constraints can hinder individuals to set up a business. Many business owners rely on own capital or capital from friends, fools and family in order to acquire required capital. In this paper, we study the role property plays for starting a business or becoming self-employed. Specifically, we investigate how property values and changes in property taxes affect the likelihood that an individual is or becomes self-employed using rich Swedish individual panel data. The paper studies the probability that an individual is or becomes self-employed using detailed individual tax return data from Sweden. The property tax reform in 2008 is utilized as a "natural experiment" to analyze whether a lower property tax increased the probability of becoming selfemployed. The reform in 2008 lowered the property tax for especially highly assessed property. Hence, the reform is predicted to reduce capital constraints for individuals with highly assessed property. Lower tax payments increase property values and consequently individual wealth, and in addition, increases disposable income as the recurrent yearly tax is reduced. The detailed data also allow us to control for many other important confounding factors. For example, we can control for other financial assets such as accumulated wealth, and capital as well as labor income. Results indicate that once we identify the effect of property value by the tax reform, property value is associated with higher probability of being self-employed but the result for becoming self-employed vanishes.
Keywords: M13; R33; R38; 330; Entrepreneurship; Self-employment; Property value